2019
DOI: 10.1186/s13011-019-0239-9
|View full text |Cite
|
Sign up to set email alerts
|

Measuring drinking motives in undergraduates: an exploration of the Drinking Motives Questionnaire-Revised in Swedish students

Abstract: BackgroundAlcohol consumption is generally high among undergraduate students and may lead to adverse consequences. Drinking motives play a vital role in the development of alcohol-related problems. The Drinking Motives Questionnaire-Revised (DMQ-R) and the short form of DMQ-R, DMQ-R SF, are widely used tools to identify drinking motives. Still, there is a need for further exploration of the instruments in different cultures and settings. The aims of this study were 1) to explore the four-factor structure of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 23 publications
2
10
0
8
Order By: Relevance
“…Adolescents who started to drink at a very young age (12-16 years) were more likely to have had a family member with alcohol problems (Table 3). When treating the age-intervals as ranked data we also observed a statistical significance (p < 0.001) with subjects having an alcoholic family member having an earlier age of first drink (alcoholic family members median 14-16 (12)(13)(14)(16)(17)(18); no alcoholic family members median 16-18 (14-16, 16-18)). Additionally, there was a statistically significant interaction between gender and the presence of alcoholic family members on the age of first alcohol use (p < 0.01, Phi and Cramer's V coefficients equals 0.15 for females and p < 0.05, Phi and Cramer's V coefficients equals 0.13 for males) indicating a weak association.…”
Section: Drinking Behavior and Taste Preferencesmentioning
confidence: 62%
See 1 more Smart Citation
“…Adolescents who started to drink at a very young age (12-16 years) were more likely to have had a family member with alcohol problems (Table 3). When treating the age-intervals as ranked data we also observed a statistical significance (p < 0.001) with subjects having an alcoholic family member having an earlier age of first drink (alcoholic family members median 14-16 (12)(13)(14)(16)(17)(18); no alcoholic family members median 16-18 (14-16, 16-18)). Additionally, there was a statistically significant interaction between gender and the presence of alcoholic family members on the age of first alcohol use (p < 0.01, Phi and Cramer's V coefficients equals 0.15 for females and p < 0.05, Phi and Cramer's V coefficients equals 0.13 for males) indicating a weak association.…”
Section: Drinking Behavior and Taste Preferencesmentioning
confidence: 62%
“…Global data are worrying, as 50–70% of 15-year-old students use alcohol, with nearly no difference between male and female [ 17 ]. It is suggested that drinking motives in young age may predict drinking patterns later in life [ 18 ]. The study conducted by Hingson et al emphasizes the need to counsel adolescents about alcohol use and to implement efficient policies that delay AC [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similar to previous results showing an association with higher typical quantity consumed per drinking occasion for coping-depression motives but not for coping-anxiety motives ( Grant et al, 2007 ), we found that the two coping motives differed in their link with both heavy drinking frequency and drinking frequency. Previous Swedish studies have also identified links between coping motives and alcohol outcomes ( Comasco et al, 2010 ; Nehlin & Oster, 2019 ). Other studies that have used the five-factor model ( Mezquita, 2016 ) have, however, not found a link to drinking between any of the two coping motives dimensions.…”
Section: Discussionmentioning
confidence: 93%
“…The Swedish adult population has been shown to primarily drink for enhancement and social motives, and less for coping and conformity motives, than the average among European countries ( RARHA, 2016 ; The Swedish Council for Information on Alcohol and Other Drugs, 2018a ). A study of undergraduate students in Sweden showed that social and enhancement motives were most common, and, along with coping motives, were also linked to hazardous drinking ( Nehlin & Oster, 2019 ).…”
mentioning
confidence: 99%
“…Drinking motivations are regarded as the most proximal predictors of both the amount and frequency of drinking, and of alcohol-related problems ( Cooper et al, 1992 ; Cooper et al, 1995 ; Kuntsche et al, 2007 ; Kuntsche et al, 2010 ). In addition, in comparison to other drinking behaviour indices, drinking motives appear to out-perform both drinking amount and/or frequency ( Brennan & Moos, 1997 ; Cooper et al, 1992 ; Cooper et al, 1995 ; Ertl et al, 2018 ; Gilson et al, 2013 ), and alcohol expectancies ( Cronin, 1997 ; Kuntsche et al, 2007 ; Kuntsche et al, 2010 ; Neighbors et al, 2007 ) in the prediction of drinking behaviour and alcohol-related problems.…”
Section: Introductionmentioning
confidence: 94%